Marcas culturais da telenovela brasileira nos mercados de Luanda - Lourenço, Augusto Alfredo (2018)
Tubiacanga, Roque Santeiro and Asa Branca are common terms for the majority of the Angolan population. These are symbolic marks resulting from intercultural interactions, hence the main focus of this dissertation is the search in the Luanda markets for remnants of the presence of the Brazilian telenovela in the Angolan imaginary, more than 40 years after the first novel Gabriela Cravo and Cinnamon. Tradition and identity, as a source of production of meanings and experiences, as well as the hybridism of culture through the influence of the mass media with prominence for television, stand out from the universe of approaches. In the context of modernity, the voice of the drum is described as the delicate vital cord through which man connects with the call of the roots of his ancestry. There is an analogy between the narrative genres of tamboralidade and television, especially with the telenovela, made of a convergence of several genres like melodrama, folklore, dithyrambo, theater and the circus. Soap operas prove to be excellent tools, not only in the entertainment process, in the activation of the mechanisms of conversation and literacy of the audience, but also as Soft Power in promoting Brazil's empathy with other countries and peoples. In order to achieve the purposes of the research, and considering the similarities of shared historical and cultural reality between Africa and Latin America, the Reception Studies were the theoretical rampart in the search for symbolic marks resulting from the process of reception and appropriation of Brazilian audiovisuals. Thus, the reflections of the researcher Jesús Martin Barbero, constitute the theoretical staff in understanding the role of the media in the relations between hegemonic culture and popular culture, as a producer of meanings, and the place of the telenovela in the process of modernization of Angolan society.